Detection of deep vein thrombosis with Doppler sonography - Kocakoc, Ercan (Springer, 2008)
[Abstract Not Available]
Keywords: Venous Thrombosis; Venography; Us; Ultrasonography; Compression; Ultrasound; Diagnosis